An Efficient Animal Model for Studying Angiogenesis of Engineered Constructs: Octet Truncal Pedicles of Rabbit - Demirtas, Y.; Engin, M. S.; Cifci, M.; Karacalar, A. (Mary Ann Liebert Inc, 2007)
…
Conference of the Tissue-Engineering-and-Regenerative-Medicine-International-Society (TERMIS-EU) -- SEP 04-07, 2007 -- London, ENGLAND